1990
DOI: 10.1002/1097-0142(19901215)66:12<2620::aid-cncr2820661226>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor localization in normal and neoplastic epithelium of the uterine cervix

Abstract: To investigate the estrogen receptor (ER) status of cells during carcinogenesis of the uterine cervix, the immunohistochemical reactivity for a monoclonal anti-ER antibody (H 222) was studied in 26 normal cervical specimens, 21 cases of cervical intraepithelial neoplasia (CIN), and 21 cases of invasive cervical carcinoma. In addition, the presence of human papillomavirus (HPV) DNA (types 6/11, 16/18, or 31/33/35) was analyzed by in situ hybridization. In the normal cervix, basal cells of the squamous epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
2
28
0
3
Order By: Relevance
“…As noted in previous studies, ESR1 expression in normal epithelium was primarily observed in the basal portions of the epithelium. 15 To determine whether HPV presence or particular type correlated with ESR1 expression, the HPV status of each tissue sample was determined using PCR amplification of DNA samples using one or more sets of consensus primers, followed by direct sequencing of the PCR products. We identified no correlation between HPV status or HPV type with loss of ESR1 expression (Supplemental Table S2 at http//ajp.amjpathol.org).…”
Section: Expression Of Esr1 Is Low In Most Invasive Cervical Carcinommentioning
confidence: 99%
“…As noted in previous studies, ESR1 expression in normal epithelium was primarily observed in the basal portions of the epithelium. 15 To determine whether HPV presence or particular type correlated with ESR1 expression, the HPV status of each tissue sample was determined using PCR amplification of DNA samples using one or more sets of consensus primers, followed by direct sequencing of the PCR products. We identified no correlation between HPV status or HPV type with loss of ESR1 expression (Supplemental Table S2 at http//ajp.amjpathol.org).…”
Section: Expression Of Esr1 Is Low In Most Invasive Cervical Carcinommentioning
confidence: 99%
“…Like the breast, the uterine cervix is a target tissue for steroid hormones and contains oestrogen receptors in endocervical epithelium, stromal cells and basal layers of squamous epithelium (Kupryjanczyk & Moller, 1988;Cano et al, 1990;Nonogaki et al, 1990). In this preliminary study we have shown, as far as we are aware for the first time, that a proportion of cervical adenocarcinomas also contain immunocytochemically detectable ER protein; this finding was associated with a good prognosis.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies using the dextran coated charcoal method (Martin et al, 1978;Ford et al, 1983;Gao et al, 1983; (Nonogaki et at., 1990) none of the six cervical adenocarcinomas examined showed ER immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] Despite some opposite results, it broadly appears that the expression of E 2 -R and P 4 -R is higher in SIL biopsies compared with normal ectocervix and Published in: American Journal of Obstetrics and Gynecology (2003), vol. 189, iss.…”
mentioning
confidence: 99%